Composition engineering of perovskite absorber assisted efficient textured monolithic perovskite/silicon heterojunction tandem solar cells. Issue 12 (9th March 2023) - He, Yongcai; Tang, Zeguo; He, Bo; Han, Changbao; Ding, Lei; Gu, Xiaobing; Zhang, Yongzhe; Yan, Hui; Xu, Xixiang
Abstract : Two-terminal monolithic tandem solar cell prepared on the commercialized silicon substrate is the most promising route. Composition engineering for perovskite top cells enables better current mismatch and morphology as well as good performance of the tandem cells. Abstract : A two-terminal (2T) perovskite/silicon heterojunction tandem solar cell (PVSK/SHJ) is considered one of the most promising candidates for next-generation photovoltaics with the possibility of achieving a power conversion efficiency (PCE) exceeding 30% at low production cost. However, the current mismatch and voltage loss have seriously decreased the performance of 2T PVSK/SHJ tandem solar cells. Here, we report the composition engineering for perovskite top cells to prepare a high performance 2T tandem cell by tuning CsBr co-evaporating rates and increasing concentrations of FAI/FABr solutions. We show that the variation in composition for the perovskite absorber effectively optimized the band gap and diminished the defects of the top cell. Our investigations reveal that the current mismatch of sub-cells was carefully tuned by introducing CsBr at varied co-evaporating rates and the voltage loss was decreased by increasing concentrations of FAI/FABr solutions. Thus, we achieved a PCE of 23.22% in two-terminal monolithic tandems with an area of 1.2 cm 2 by tuning the composition of the perovskite absorber.